Experience of urgent surgical thrombolectomy of high-risk acute massive pulmonary embolism under parallel cardiopulmonary bypass: a case report - V. V. Osaulenko; K. O. Chmul; R. I. Budaghov (Сучасні медичні технології)
Massive acute pulmonary embolism is a rare and life-threatening condition that cardiac surgeons may encounter in their clinical practice. Although systemic thrombolysis is often prescribed in critically ill patients to improve pulmonary perfusion and reduce right ventricular afterload, surgical treatment is an objective alternative when thrombolytic therapy is ineffective or impossible.